Communication of the Religious Harmony Forum (FKUB) in developing religious moderation in Salatiga City - Hidayanti, Ulfah; Ali, Mukti (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
Religious moderation is part of the 2020-2024 National Medium-Term Development Plan (RPJMN). Religious moderation is a form of government effort to counteract violent extremism. This program must be supported by all elements in Indonesia, such as society, government, and interfaith organizations such as the Forum for Religious Harmony (FKUB). The city of Salatiga is a portrait of diversity because of its diversity of cultures and religions. Communication is vital in the organization's center, uniting and integrating all elements to achieve organizational goals. This study aims to determine the communication the Forum for Religious Harmony (FKUB) uses in developing religious moderation in Salatiga City. This study uses a qualitative method with an interpretive approach and data collection techniques using interviews, observation, and documentation. The results of the study show that there are five communications carried out by the Forum for Religious Harmony (FKUB) in developing religious moderation in Salatiga City, namely (1) social services, (2) counseling/socialization, (3) mock studies/work visits, (4) intensive involvement in the activities of other agencies and (5) building religious tourism sites. The obstacles faced by FKUB in developing religious moderation in Salatiga City are (1) the lack of Human Resources (HR) and (2) the lack of budgetary funds provided by the government. This study contributes to developing an interfaith organizational communication model for creating religious harmony in society. ***Moderasi beragama merupakan Rencana Pembangunan Jangka Menengah Nasional (RPJMN) tahun 2020-2024. Moderasi beragama adalah bentuk usaha pemerintah dalam menangkal adanya ekstremisme-kekerasan. Program ini harus didukung oleh seluruh elemen yang ada di Indonesia seperti masyarakat, pemerintah dan organisasi-organisasi lintas agama seperti Forum Kerukunan Umat Beragama (FKUB). Kota Salatiga adalah salah satu kota yang menjadi potret kemajemukan karena keanekaragaman budaya dan agama yang ada didalamnya. Komunikasi memegang peranan penting dalam pusat organisasi untuk menyatukan dan mengintegrasikan semua elemen untuk mencapai tujuan organisasi Penelitian ini bertujuan untuk mengetahui komunikasi yang digunakan Forum Kerukunan Umat Beragama (FKUB) dalam mengembangkan moderasi beragama di Kota Salatiga. Penelitian ini menggunakan metode kualitatif dengan pendekatan interpretif. Adapun teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Hasil penelitian bahwa ada lima komunikasi yang dilakukan Forum Kerukunan Umat Beragama (FKUB) dalam mengembangkan moderasi beragama di Kota Salatiga yaitu (1) bakti sosial, (2) penyuluhan/sosialisasi, (3) studi tiru/kunjungan kerja, (4) pelibatan intensif dalam kegiatan instansi lain dan (5) membangun tempat wisata religi. Hambatan yang dihadapi FKUB dalam mengembangkan moderasi beragama di Kota Salatiga adalah (1) minimnya Sumber Daya Manusia (SDM) dan (2) kurangnya anggaran dana yang diberikan oleh pemerintah. Studi ini berkontribusi bagi pengembangan model komunikasi organisasi lintas agama dalam menciptakan harmoni beragama dalam masyarakat.